2020
DOI: 10.1101/2020.08.25.20181545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“I walk around like my hands are covered in mud”: food safety and hand hygiene behaviours of Canadians during the COVID-19 pandemic

Abstract: Objectives: To investigate how and why Canadians engaged in different food handling and hand hygiene behaviours during the COVID-19 pandemic. Methods: Seven online, text-based focus groups were conducted with a total of 42 participants. Eligible participants included adults living in Canada that prepared meals at home at least once per week. Focus groups took place from May-June 2020 and followed a semi-structured question guide. Participants were asked about their practices relating to food preparation habit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…In the present study, the survey data and focus groups confirmed an increase in hand washing during the pandemic compared with before the pandemic. This finding is similar to recent studies focused on hand hygiene and the COVID-19 pandemic and previous studies about the H1N1 pandemics ( 30 , 55 ) . The increase in hand washing during these health events may be due to the emphasis on this practice as a preventative measure for diseases in general ( 17 ) .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the survey data and focus groups confirmed an increase in hand washing during the pandemic compared with before the pandemic. This finding is similar to recent studies focused on hand hygiene and the COVID-19 pandemic and previous studies about the H1N1 pandemics ( 30 , 55 ) . The increase in hand washing during these health events may be due to the emphasis on this practice as a preventative measure for diseases in general ( 17 ) .…”
Section: Discussionsupporting
confidence: 93%